Biological Characterization and Glucosinolate Degradation Mechanisms of Bacillus subtilis BSY82 in Rapeseed Meal - Hong-yu Lu; An-Ning Shi; Jun Wang; Li-Juan Liu; Jiang-Yi Tang; Ya-Jun Wang; Xue-Zhi Zhu; De-Feng Zhang; Li-Yan Liu; Qing Wang (Aquaculture Nutrition)
Glucoside is the main antinutritional factor (ANF) of rapeseed meal. In the present study, a bacterium with high efficiency in degrading rapeseed glucoside was screened from pond water. The initial concentration of 1.0 × 107 CFU/mL bacterial solution was added to rapeseed meal and fermented for 48 h with a degradation rate of glucoside and isothiocyanate of 67% and 54%, respectively. BSY82 was identified by PacBio third-generation sequencing, and its biology was analyzed. Results showed that BSY82 belongs to Bacillus subtilis. The total length of genome was 4,242,094 bp, among which 89% was coding genes (3,777,298 bp). No virulence factors were predicted, based on a comparative analysis of the strain’s coding genes against known virulence factor databases. Functional analysis showed that BSY82 had the ability to produce myrosinase. The activity of myrosinase in the crude enzyme solution of the strain was 1.67 and 2.12 μmol/min by spectrophotometry and high-performance liquid chromatography (HPLC). The results indicated that BSY82 strain could be used as the optimal material in rapeseed meal fermentation detoxification process.